Case Report: Hypereosinophilic syndrome vs. patent foramen ovale as etiopathogenetic contributors to stroke - Liu, Xiangjuan; Sun, Congcong; An, Guipeng; Cao, Lili; Meng, Xiao (Frontiers in Cardiovascular Medicine, 2024)
Hypereosinophilic syndrome (HES), characterized by an increased number of eosinophils in tissues and/or blood, presents with heterogeneous clinical manifestations. Studies have shown that HES can affect the nervous system and may be associated with cerebral infarction. Patent foramen ovale (PFO) is the most common congenital intracardiac defect that can cause right-to-left shunting and contribute to the paradoxical embolization of venous emboli, and even lead to stroke. We report the case of a young man who presented with cerebral infarction accompanied by both HES and PFO. The patient underwent thorough evaluation to determine the source of emboli and the potential pathogenesis. In this case, HES was confirmed and glucocorticoid treatment was conducted. Direct imaging using optical coherence tomography (OCT) confirmed that the embolus originated from the PFO. Therefore, we performed PFO occlusion. The patient recovered well, and no new cerebral infarction was observed at 6-month follow-up. Based on the results of our study, we conclude that it is important to consider unusual etiologies of cerebral infarction, particularly in younger patients.